Teater sebagai Media Komunikasi Lingkungan: Studi Kasus pada Pertunjukan Teater Kafha Re(kognisi) - Farah Novda Rahmadani; Ahmad Mulyana (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
This study aims to explore the creative process of the Teater Kafha team in raising stakeholder awareness regarding environmental issues through the theater performance "Re(kognisi)". The focus of this research is to understand how environmental messages are constructed within the performance, how communication strategies are manifested through elements of the performance such as the script, symbols, actors, artistic direction, and audience interaction, and how the audience interprets and responds to these messages. This research employs a qualitative approach with a case study method, involving in-depth interviews, observation, and documentation for data collection. The results indicate that Teater Kafha develops a collaborative creative process by combining the ideas of the director, artistic team, and actors to translate environmental issues into communicative stage symbols. Communication strategies are realized through the composition of a reflective script, the use of strong visual symbols, deep actor expressions, and spatial arrangements that create an immersive experience for the audience. Audience responses to the performance show a new understanding and critical reflection on environmental issues, particularly regarding the impact of a geothermal project that serves as the backdrop of the performance. This study emphasizes that performing arts, particularly theater, can function as an alternative communication medium that effectively articulates social and environmental issues. Through this approach, theater plays a significant role in broadening public awareness of important and urgent environmental issues.